Faktor Risiko Kejadian Presbiopia Dini - Hajri Rabbani1, Nur; Utami Helisarah, Desi; Suparni, Suparni; Pamungkas, Motris (stikes dharma husada bandung, 2021)
The most significant risk factor for presbyopia is age. However, when symptoms of presbyopia occur earlier than usual, it is called premature presbyopia. Premature presbyopia is a reduction in the ability to accommodate near-eye vision that is faster than expected. This research is an attempt to find out what are the risk factors that can causes premature presbyopia. To conduct a literature review to determine the age distribution of premature presbyopia and determine risk factors associated with premature presbyopia. This research was conducted by the method of literature review which is a method used to collect data or sources related to the topics raised in a study. Based on the results of literature review from several journals and research results show that the age range of patients with premature presbyopia is at the age range of 36-39 years. The risk factors that affect the incidence of premature presbyopia are: sex (gender), gadget users and near work, smoking and tobacco use, and refractive errors. It is hoped that this literature review can be used as an initial prediction in the management of basic eye examinations seen from their daily activities and lifestyle and it is also hoped that this literature review can be a reference for refractionist opticiant in dealing with patients who have near vision complaints so as not to hesitate in providing correction of additions to patients with age <40 years. It is hoped that this literature review can be used as an initial prediction in the management of basic eye examination seen from their daily activities and lifestyle.